Platelet tissue factor activity and membrane cholesterol are increased in hypercholesterolemia and normalized by rosuvastatin, but not by atorvastatin - Panes, Olga; González, César; Hidalgo, Patricia; Valderas, Juan P.; Acevedo, Mónica; Contreras, Susana; Sánchez, Ximena; Pereira, Jaime; Rigotti, Attilio; Mezzano, Diego (Atherosclerosis, 2017)
High plasma LDL-cholesterol (LDL-C) and platelet responses have major pathogenic roles in atherothrombosis. Thus, statins and anti-platelet drugs constitute mainstays in cardiovascular prevention/treatment. However, the role of platelet tissue factor-dependent procoagulant activity (TF-PCA) has remained unexplored in hypercholesterolemia. We aimed to study platelet TF-PCA and its relationship with membrane cholesterol in vitro and in 45 hypercholesterolemic patients (HC-patients) (LDL-C >3.37 mmol/L, 130 mg/dL) and 37 control subjects (LDL-C <3.37 mmol/L). The effect of 1-month administration of 80 mg/day atorvastatin (n = 21) and 20 mg/day rosuvastatin (n = 24) was compared. Platelet TF-PCA was induced by GPIbα activation with VWF-ristocetin. Cholesterol-enriched platelets in vitro had augmented aggregation/secretion and platelet FXa generation (1.65-fold increase, p = 0.01). HC-patients had 1.5-, 2.3- and 2.5-fold increases in platelet cholesterol, TF protein and activity, respectively; their platelets had neither hyper-aggregation nor endogenous thrombin generation (ETP). Rosuvastatin, but not atorvastatin, normalized platelet cholesterol, TF protein and FXa generation. It also increased slightly the plasma HDL-C levels, which correlated negatively with TF-PCA. Platelets from HC-patients were not hyper-responsive to low concentrations of classical agonists and had normal PRP-ETP, before and after statin administration. However, washed platelets from HC-patients had increased membrane cholesterol, TF protein and TF-PCA. The platelet TF-dependent PCA was specifically expressed after VWF-induced GPIbα activation. Rosuvastatin, but not atorvastatin treatment, normalized the membrane cholesterol, TF protein and TF-PCA in HC-patients, possibly unveiling a new pleiotropic effect of rosuvastatin. Modulation of platelet TF-PCA may become a novel target to prevent/treat atherothrombosis without increasing bleeding risks. •Platelet tissue factor (TF) initiates the clotting process.•TF activation is induced by VWF binding to GPIbα.•Platelet FXa generation in hypercholesterolemia (HC) is abnormally high.•Rosuvastatin decreases platelet cholesterol and TF-induced clotting in HC.•HDL and platelet TF activity correlate negatively in non-treated HC-patients.